2014
DOI: 10.1002/cplu.201402080
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Processing of Ceria Nanoparticles inside Liver: Impact on Free‐Radical Scavenging Activity and Oxidative Stress

Abstract: The cytotoxicity of ceria ultimately lies in its electronic structure, which is defined by the crystal structure, composition, and size. Despite previous studies focused on ceria uptake, distribution, biopersistance, and cellular effects, little is known about its chemical and structural stability and solubility once sequestered inside the liver. Mechanisms will be presented that elucidate the in vivo transformation in the liver. In vivo processed ceria reveals a particle-size effect towards the formation of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
90
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 73 publications
(104 citation statements)
references
References 45 publications
13
90
1
Order By: Relevance
“…2). Inflammatory responses have been previously shown to activate abundant ferritin formation in localized regions with invader nanoparticles [3]. The current study shows for the first time that the same process occurs after in vivo delivery of ions, followed by their transport, and precipitation.…”
supporting
confidence: 64%
“…2). Inflammatory responses have been previously shown to activate abundant ferritin formation in localized regions with invader nanoparticles [3]. The current study shows for the first time that the same process occurs after in vivo delivery of ions, followed by their transport, and precipitation.…”
supporting
confidence: 64%
“…The Cd core of the QDs is often toxic-this has to be taken into account in the interpretation of QD bio-distribution and NM-mediated effects (Sanwlani et al 2014, Silva et al 2014, Zhan and Tang 2014. Finally, Ce NMs are distributed much like insoluble NMs, but it has been demonstrated that they are oxidised and re-crystallised as oxidised NMs in the liver (Graham et al 2014). Therefore, it is important to understand the nature of NMs and distinguish between material types (virtually insoluble, slowly and rapidly soluble NMs) in order to gain a better understanding of their ability to translocate, bio-persist and induce of toxicity in secondary organs (Table 4).…”
Section: Discussionmentioning
confidence: 96%
“…Clouds of 1 to 3 nm, (111) and (200) faced, crystalline ceria near the partially biodegraded nanoceria were seen, suggesting a dissolution-precipitation process. EELS showed increased surface Ce 3+ consistent with ultrafine nanoceria particles, suggesting greater anti-oxidant potential 45 . These observations suggest nanoceria bioprocessing to a more stable, potentially more beneficial, nanoceria form.…”
Section: Systemic Nanoceria Exposurementioning
confidence: 91%